Interrelation between the content of magnesium in the blood of the strain stenocardia patients of different temperament and anxiety and tension degree of the Earth magnetic field - G. A. Usenko; A. G. Usenko; D. V. Vasendin; N. A. Schakirova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
During the magnetic storms magnesium content decreases and frequency of angina pectoris attacks increases minimally in the lowanxiety cholerics and maximally in the highanxiety melancholics and phlegmatics. The latter are the groups at risk of developing complications of coronary heart disease.